Feminist Temporality and the Negotiation of Gender Identity and Agency in Zen Cho’s Black Water Sister - Fang, Sirui; Chin, Grace V. S. (SARE: Southeast Asian Review of English, 2024)
Using Steven Hitlin and Glen Elder’s theory of temporal agency and Elizabeth Grosz’s theory of feminist temporality, this article examines complex temporality and three female characters’ agency and negotiation with Confucian patriarchal gender norms in Zen Cho’s Black Water Sister (2021). Across different generations, three female characters—one millennial diasporic Malaysian Chinese girl, a local Malaysian Chinese ghost, and a Malaysian Chinese ghost/goddess—experience supernatural journeys to challenge Confucian patriarchal discourse. Diverse strategies of female agency concerning different temporal dimensions are reflected through the three female characters’ daily behaviours, resistance, and life choices. These behaviours and choices are shaped by their individual experiences and Confucian patriarchal gender norms at different times. By exercising female agency, three female characters immerse themselves deeply in the past or find a balance between memory and forgetting in order to heal the traumatic past or create a feminist future.